PRISLAMISM, RADICALIZATION AND DERADICALIZATION IN CANADA - Mubin Shaikh (The Journal of Intelligence, Conflict and Warfare, 2024)
On November 13, 2023, Professor Mubin Shaikh presented Prislamism, Radicalization, and Deradicalization in Canada at the West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were that Prislamism, thought of as a route to radicalization, is a blend of Islamic theory and concepts that advocates for violence toward institutions of incarceration. The prison systems in both Muslim and Western nations provide a breeding ground for radicalization through both their physical conditions and the social dynamics of custody. Combating radicalization in prisons requires robust training and a steadfast adherence to the law on the part of practitioners.